Rules for stealing stars - Haydu, Corey Ann (Katherine Tegen Books, 2017)
Silly is the youngest sister in her broken family. She cannot remember a time when mother didn't drink and father didn't pretend things were okay, nor when her three older sisters weren't seeming to keep secrets from her. One day, though, Silly's sisters bring her into their secret--a hidden, magical place where they can escape from the troubles of home. However, Silly finds soon that this magic has its own dark truths to ponder.